Carcinogenic and non-carcinogenic risk estimation of indoor TVOCs, RSPM, FPM and SFPM on young women dwellers: a case study from the capital city of Uttar Pradesh, India - Farheen Zehra; Samridhi Dwivedi; Mohd Akbar Ali; P. S. Rajinikanth; Alfred Lawrence (Discover Applied Sciences)
Abstract Total volatile organic compounds (TVOCs), respiratory suspended particulate matter (RSPM-PM10), fine particulate matter (FPM-PM2.5) and sub-fine particulate matter (SFPM-PM1) have been found to exert negative impact on the women health. This study was conducted to see the effect of indoor RSPM, FPM, SFPM and TVOCs on women health predominantly on young women dwellers (specifically categorized into pre-teenagers i.e., 8–12 years, teenagers i.e., 13–19 years and post-teenagers i.e., 20–21 years). Indoor monitoring was conducted from November 2022 to February 2023 in six different urban households of Lucknow, capital city of Uttar Pradesh state of India. Envirotech APM 550 for RSPM and FPM, APM 577 for SFPM and portable sensor-based instrument (BR-SMART) were used to measure TVOCs. The highest average indoor concentrations was found to be 250.1 ± 14.11 µg/m3 (PM10) at Rajajipuram, 140.62 ± 19.71 µg/m3 (PM2.5) at Indranagar, 27.60 ± 1.87 µg/m3 (PM1) and 934 ± 70.41 µg/m3 (TVOCs) at Kaiserbagh.Health risk assessment was also determined using average daily dose (ADD), excess lifetime cancer risk (ELCR) and hazard quotient (HQ) for carcinogenic and non-carcinogenic risk. ELCR values for PM1 and PM2.5 surpassed the permissible limit in every house and HQ values also exceeded the minimum allowable value for 20–21 year age group at all of the locations, indicating substantial health risk from exposure. International Committee of Radiological Protection Model (ICRP) and Multiple Path Particle Dosimetry (MPPD) model were used to see the regional deposition of PMs on the young women dwellers. To elucidate the spatial dynamics of these pollutants, the Inverse Distance Weighting (IDW) interpolation technique was employed. Additionally, site-specific analysis of PM mass ratios (PM2.5/PM10, PM1/PM2.5 and PM1/PM10) elucidated the particle size distribution and their sources, significantly enhancing the scientific understanding of aerosol dynamics in these urban settings.